PARIWISATA BERKELANJUTAN PADA DANAU TIMBANG BUNGA PENGANTIN DESA SUNGAI SORIK KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Meyliza Mutia Syapwi; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Tourism Object of Lake Timbang Bunga Pengantin is a tourist destination located in Sungai Sorik Village, Kuantan Hilir District, Kuantan Singingi Regency. The lake which has an area of 15 hectares is managed by BUMDES Aur Kuning in the form of a langang by the government of Sungai Sorik Village. In its management, BUMDES has several problems, namely in planning the lack of local community participation, promotions that are still only micro, insufficient budget, and the existence of the Covid-19 pandemic which has forced several events to be stopped. The purpose of this study is to determine the management of sustainable tourism on Lake Timbang Bunga Bride in Sungai Sorik Village, Kuantan Singingi Regency, as well as the inhibiting factors and supporting factors for sustainable tourism on the Lake Timbang Bunga Pengantin in Sungai Sorik Village, Kuantan Singingi Regency. The theoretical concept used in this study is the concept of Sustainable Tourism and 1 Made Adi Kampama 2017. The method used by researchers in this study is qualitative, and researchers conduct interviews, observations, and documentation in carrying out data collection techniques. The results obtained in this study are that the management carried out by BUMDES Aur Kuning has carried out performance according to the indicators set by the researchers, but in some cases there are still obstacles experienced by BUMDES, so that the management carried out is still not optimal. Keywords: Management, Sustainable Tourism, Lake Timbang Bunga Pengantin